Evidence of diffuse cerebellar neuroinflammation in multiple sclerosis by 11C-PBR28 MR-PET. (May 2020) - Barletta, Valeria T; Herranz, Elena; Treaba, Costantina A; Ouellette, Russell; Mehndiratta, Ambica; Loggia, Marco L; Klawiter, Eric C; Ionete, Carolina; Jacob, Sloane A; Mainero, Caterina
Background: Activated microglia, which can be detected in vivo by 11 C-PBR28 positron emission tomography (PET), represent a main component of MS pathology in the brain. Their role in the cerebellum is still unexplored, although cerebellar involvement in MS is frequent and accounts for disability progression. Objectives: We aimed at characterizing cerebellar neuroinflammation in MS patients compared to healthy subjects by combining 11 C-PBR28 MRI-Positron Emission Tomography (MR-PET) with 7 Tesla (T) MRI and assessing its relationship with brain neuroinflammation and clinical outcome measures. Methods: Twenty-eight MS patients and 16 healthy controls underwent 11 C-PBR28 MR-PET to measure microglia activation in normal appearing cerebellum and lesions segmented from 7 T scans. Patients were evaluated using the Expanded Disability Status Scale and Symbol Digit Modalities Test. 11 C-PBR28 binding was assessed in regions of interest using 60–90 minutes standardized uptake values normalized by a pseudo-reference region in the brain normal appearing white matter. Multilinear regression was used to compare tracer uptake in MS and healthy controls and assess correlations with clinical scores. Results: In all cerebellar regions examined, MS patients showed abnormally increased tracer uptake, which correlated with cognitive and neurological disability. Conclusion: Neuroinflammation is widespread in the cerebellum of patients with MS and related to neurological disability and cognitive impairment.